HEDONISME DALAM PROMO PROGRAM SINETRON JAKARTA LOVE STORY"VERSI ALYSA" - Kusumawati, Nina (Jurnal Public Relations (J-PR), 2020)
This research is entitled Hedonism in Promo Program Sinetron "Jakarta Love Story"Alysa's version. The object of research in this study is Promo Program Sinetron "Jakarta Love Story"Alysa's version which tells about the life of a woman named Alysa who is a girl with a hedonistic lifestyle. This research is qualitative research using Charles Sanders Pierce's semiotic analysis with the triangle of a meaning theory which develops a meaning triangle consisting of signs, objects, and interpretants. The results of this study indicate that the promo for Alysa's version of the soap opera Jakarta Love story program. This program promo imagines a woman with a hedonic lifestyle with a barely-fitting brain who can survive by looking for a rich man who relies on beauty. The hedonist lifestyle is depicted by the character Alysa through scenes showing off luxury and branded goods